2006
DOI: 10.1079/pgr2005104
|View full text |Cite
|
Sign up to set email alerts
|

Traitmill™: a functional genomics platform for the phenotypic analysis of cereals

Abstract: The improvement of quality and quantitative traits in industrial crops is among the most important goals in plant breeding. Many traits of interest are controlled by multiple genes and improvements have so far only been obtained through conventional breeding. The use of biotechnological tools to modify quantitative traits is highly challenging. CropDesign has developed TraitMill™, an automated plant evaluation platform allowing high-throughput testing of the effect of plant-based transgenes on agronomically va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 9 publications
0
30
0
2
Order By: Relevance
“…Commercial platforms, including the Scanalyzer series from Lemnatec (http:// www.lemnatec.com/products/; accessed February 2016) and the Traitmill platform from CropDesign (http:// www.cropdesign.com/general.php; accessed February 2016), have gained adoption in the research community and have promoted the development of additional software (beyond that which the respective companies provide) to analyze the images produced by the platform (Reuzeau, 2007;Hartmann et al, 2011;Fahlgren et al, 2015a). A variety of noncommercial platforms and methods developed by the research community also exist and have been demonstrated to perform well (White et al, 2012;Fiorani and Schurr, 2013;Sirault et al, 2013;Pound et al, 2014).…”
mentioning
confidence: 99%
“…Commercial platforms, including the Scanalyzer series from Lemnatec (http:// www.lemnatec.com/products/; accessed February 2016) and the Traitmill platform from CropDesign (http:// www.cropdesign.com/general.php; accessed February 2016), have gained adoption in the research community and have promoted the development of additional software (beyond that which the respective companies provide) to analyze the images produced by the platform (Reuzeau, 2007;Hartmann et al, 2011;Fahlgren et al, 2015a). A variety of noncommercial platforms and methods developed by the research community also exist and have been demonstrated to perform well (White et al, 2012;Fiorani and Schurr, 2013;Sirault et al, 2013;Pound et al, 2014).…”
mentioning
confidence: 99%
“…In addition, some models require various types of high-throughput data. In this respect, the rapid development of large-scale phenotyping technologies may provide part of the solution (Granier et al, 2006;Reuzeau et al, 2006;Tisné et al, 2013).…”
Section: Applying Contemporary Crop Modeling Approaches To a Thalianamentioning
confidence: 99%
“…These nondestructive systems are equipped with computer algorithms to analyze the images and calculate hypocotyl length, apical hook opening, and phototropic bending. For older plants, some automated platforms can capture the image and weigh each plant (Granier et al, 2006;Reuzeau et al, 2006;Tisné et al, 2013). Besides the whole-plant monitoring systems described above, high-resolution imaging technologies at the organ and cellular level are also under rapid development.…”
Section: The Data Gapmentioning
confidence: 99%
“…To demonstrate the methods developed in this paper, we will use a real example of transgenic screening experiments using TraitMill, a high-throughput screening platform for rice (Reuzeau et al 2005). This example will be used throughout and be further elaborated in the last section of the paper.…”
Section: Gene Effects: a Range Of Phenotypesmentioning
confidence: 99%